Airway Interleukin-33 and type 2 cytokines in adult patients with acute asthma. (July 2018) - Poulsen, Nadia Nicholine; Bjerregaard, Asger; Khoo, Siew-Kim; Laing, Ingrid A.; Le Souëf, Peter; Backer, Vibeke; Rapley, Laura; Cohen, Suzanne E.; Barrett, Lucy; Thompson, Philip; Baltic, Svetlana; Porsbjerg, Celeste
Abstract: Background: Several animal studies, and one inoculation study in adult asthmatics have shown that interleukin-33 (IL-33) is a major contributor to type-2 inflammation in acute asthma. However, the link between IL-33 and type-2 inflammation has not been shown in naturally occurring asthma exacerbations. Objectives: To determine if airway IL-33 is associated with type-2 inflammation measured by type-2 cytokines, FeNO and sputum eosinophils in patients presenting to the Emergency Department with an asthma exacerbations. Methods: Adult patients hospitalized due to acute asthma were enrolled. Upper airways were sampled with nasal swabs and lower airways with induced sputum. Cytokines were measured at protein level using a Luminex ® assay and mRNA expression level using droplet-digital-PCR. Airway sampling was repeated four weeks after exacerbation. Results: At the time of exacerbation, upper airway IL-33 correlated with upper airway IL-5 and IL-13 (R = 0.84, p < 0.01 and R = 0.76, p < 0.01, respectively) and with lower airway IL-13 (R = 0.49, p = 0.03). Similar associations were observed for mRNA expression. Lower airway IL-33 positively correlated with lower airway IL-13 (R = 0.84, p < 0.01). IL-13 and IL-33 were positively correlated with FeNO, and IL-5 with eosinophils. The association between IL-33 and type-2 cytokines were still present four weeks after exacerbation. Conclusion: This is the first study to demonstrate that airway IL-33 is associated with type-2 cytokines in naturally occurring asthma exacerbations in adults, providing in vivo evidence supporting that IL-33 may be driving type-2 inflammation in acute asthma. Thus supporting IL-33 as a potential future drug target due to its role, upstream in the immunological cascade. Highlights: IL-33 correlates to type 2 cytokines in hospitalized patients with acute asthma. Airway IL-13 and IL-33 positively correlate with fractional exhaled nitric oxide. Airway IL-5 correlates to blood eosinophils in naturally occurring acute asthma.